Perspectives on sociodemographic factors and solid waste management in the district of Chachapoyas - Coronel-Chugden, Jose-Walter; Huaman-Romani, Yersi-Luis; Ayay-Arista, Guido; Flores-Castillo, Marcos-Marcelo; Cahuana-Lipa, Rocio; Machaca-Mamani, Julio-Cesar (International Journal of Innovative Research and Scientific Studies, 2023)
The accelerated production of solid waste in the urban-rural context requires studies to optimize the environmental pollution gap. The objective of the study is to know the perspectives of sociodemographic factors and solid waste management in the district of Chachapoyas. The research is of a causal descriptive type at an explanatory level. The sample is composed of 382 families obtained through probabilistic sampling. The survey technique was used, and the questionnaire was a valid and reliable instrument (Cronbach’s alpha = 0.777). The results indicate that the sociodemographic profile has a significant effect (p<0.05) on solid waste management, including economic status, age, occupation, education level, monthly income, area of residence, and number of persons per household. In addition, it was found that solid waste management in the city has a regular level of performance. However, there are gaps that need to be addressed in the following order of priority: storage, final disposal, generation, treatment, and recycling. In conclusion, solid waste management in the city of Chachapoyas is average, indicating the need to address these gaps in the formulation of new public policies.